Social Media Use and Psychosocial Implications of Covid-19 Pandemic among Adolescent Students - Jincy T. C.; A. Enoch; Jesmy P. J (Research and Education)
COVID-19 has been an unexpected crisis period, directing the minds of people into ear and anxiety. Social distancing being a major preventive activity to overcome this contagious disease, which led to affect all aspects of life worldwide. The new pandemic experience has highly affected the psychosocial aspects of adolescents. Social media has become the centre of communication during this isolated period. Classroom learning has changed to virtual teaching during the lockdown period. A research was conducted to analyse the influence of COVID-19 on adolescents' social media usages. The study focused on social media usage and its impact on adolescents' psycho-social behaviour. Participants were 287 adolescent students from 6 mostly affected states of India. Data gathering was carried out during the COVID -19 Lockdown in India with a self-structured online questionnaire. The respondents have not agreed that online classes are better than classroom learning. There was a high increase in the use of social media during the lockdown period. Social media has helped them to cope with the isolated situation and has led to an increase in their creativity. WhatsApp, YouTube, Facebook, and Instagram are the prominent social media used during this pandemic situation.